2014
DOI: 10.1016/j.neubiorev.2014.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Impairments of multisensory integration and cross-sensory learning as pathways to dyslexia

Abstract: Two sensory systems are intrinsic to learning to read. Written words enter the brain through the visual system and associated sounds through the auditory system. The task before the beginning reader is quite basic. She must learn correspondences between orthographic tokens and phonemic utterances, and she must do this to the point that there is seamless automatic ‘connection’ between these sensorially distinct units of language. It is self-evident then that learning to read requires formation of cross-sensory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 118 publications
(125 reference statements)
5
65
0
1
Order By: Relevance
“…Multisensory integration occurs over a restricted time window [73,96] that may be susceptible to variability in neural spike activity and learning multisensory associations relies on spike timing dependent synaptic plasticity during critical periods of development. Considering the number of possible paths to disrupted multisensory integration and its sensitivity on neural timing, deficits in multisensory processing are expected to be a reliable feature of RD and several studies have reported deficits in print-speech integration in RD [45,95,97,98]. …”
Section: Reading-related Consequences Of Neural Noise Observed In Rdmentioning
confidence: 99%
“…Multisensory integration occurs over a restricted time window [73,96] that may be susceptible to variability in neural spike activity and learning multisensory associations relies on spike timing dependent synaptic plasticity during critical periods of development. Considering the number of possible paths to disrupted multisensory integration and its sensitivity on neural timing, deficits in multisensory processing are expected to be a reliable feature of RD and several studies have reported deficits in print-speech integration in RD [45,95,97,98]. …”
Section: Reading-related Consequences Of Neural Noise Observed In Rdmentioning
confidence: 99%
“…Given that adequate associations between graphemes and phonemes occur in narrow time windows (Froyen et al, 2008), a cross-modal deficit that results in the widening of audiovisual temporal windows could impair the development of such associations and, as a consequence, reading-that is, it could hamper the formation of adequate representations, creating ambiguity in the correspondences between graphemes and phonemes (Wallace & Stevenson, 2014). This could result in reductions in the speed with which printed representations are decoded (Hairston et al, 2005) and lead to more errors in the accurate pairing of orthography and speech sounds (Hahn, Foxe, & Molholm, 2014). As an alternative, it is possible that readers with dyslexia experience difficulties in the uptake of information and extend their temporal windows to compensate for the difficulties in sensory processing.…”
Section: Discussionmentioning
confidence: 99%
“…Accurately combining information from multiple senses, multisensory integration, improves our ability to function in daily life. Importantly, disruptions or alterations in multisensory integration have been associated with a number of developmental disorders (Hahn et al, 2014; Postmes et al, 2014; Wallace and Stevenson, 2014; Cascio et al, 2016). Several bottom-up features of sensory stimuli (known as the principles of multisensory integration) have been clearly demonstrated to influence the likelihood of multisensory integration: unisensory stimuli are most likely to be integrated if they share a high temporal and spatial correspondence and have low efficacy.…”
Section: Introductionmentioning
confidence: 99%